Optimization of Organic Waste Management with a Circular Economy Approach : The Case of Food Recycling in Bantul Regency, Indonesia - Hamdani, Rizki; Ash Shidiqie, Jannahar Saddam; Priyadi, Unggul; Dinurri’anah, Umi; Adli, Akmal Inan Hafidh (Jurnal Pengabdian UNDIKMA, 2025)
The purpose of this community service activity is to encourage and increase community empowerment in managing waste, increase community income, and open up employment opportunities in the Griya Cendekia YBW UII Fostered Village, Bantul, DIY. In this community service activity, a circular economy approach is applied by empowering the community. This program involves 25 participants through maggot cultivation training and organic waste management to produce eco-enzyme products. The methods used include stages of socialization, training, and technical assistance. The results of the community service show that this activity improves the community's ability to manage organic waste productively, producing products such as laundry soap, facial soap, and hand sanitizer. This activity concludes that organic waste management through maggot cultivation and eco-enzyme production not only supports environmental sustainability but also creates new economic opportunities for the community.